2017
DOI: 10.1371/journal.pone.0180667
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical insight into thermally induced functional inactivation of firefly luciferase

Abstract: Luciferase is the key component of light production in bioluminescence process. Extensive and advantageous application of this enzyme in biotechnology is restricted due to its low thermal stability. Here we report the effect of heating up above Tm on the structure and dynamical properties of luciferase enzyme compared to temperature at 298 K. In this way we demonstrate that the number of hydrogen bonds between N- and C-domain is increased for the free enzyme at 325 K. Increased inter domain hydrogen bonds by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…amber-stop codon was placed at site K529 of fLuc (fLuc529TAG-rLuc), where a critical lysine residue orients the substrate and stabilizes the adenylated substrate during catalysis through a hydrogen-bonding interaction with the phosphate oxygen. 31 Caging this lysine blocks enzymatic activity, and small molecule-induced decaging results in full activation of fLuc through the formation of the wild-type active site (Figure 2B). 32 Previous studies of decaging PABK with a panel of phosphines in mammalian cells found that 2-(diphenylphosphinyl)benzamide (2DPBM) showed the fastest reaction rate and no toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…amber-stop codon was placed at site K529 of fLuc (fLuc529TAG-rLuc), where a critical lysine residue orients the substrate and stabilizes the adenylated substrate during catalysis through a hydrogen-bonding interaction with the phosphate oxygen. 31 Caging this lysine blocks enzymatic activity, and small molecule-induced decaging results in full activation of fLuc through the formation of the wild-type active site (Figure 2B). 32 Previous studies of decaging PABK with a panel of phosphines in mammalian cells found that 2-(diphenylphosphinyl)benzamide (2DPBM) showed the fastest reaction rate and no toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the analysis of small molecule control of enzyme function using PABK, we measured the fLuc activity. The amber-stop codon was placed at site K529 of fLuc (fLuc529TAG-rLuc), where a critical lysine residue orients the substrate and stabilizes the adenylated substrate during catalysis through a hydrogen-bonding interaction with the phosphate oxygen . Caging this lysine blocks enzymatic activity, and small molecule-induced decaging results in full activation of fLuc through the formation of the wild-type active site (Figure B) .…”
Section: Resultsmentioning
confidence: 99%
“…To study the effect of local conformational constraint on the biochemical properties of luciferase, we investigated the thermal stability of representative luciferases, which has been related to the dynamic behavior of firefly luciferase. 38 As shown in Fig. 6a, incubation of wild-Page 15 of 34 CCS Chemistry type luciferase and luciferase containing 6 at 37 o C in 50 mM Tris-HCl, pH 7.4, for 80 minutes resulted in a steady loss in their ability to produce light, as aliquots were taken as a function of time and then treated with luciferin, ATP and Mg 2+ .…”
Section: Effects Of Local Conformational Constraint On the Properties...mentioning
confidence: 99%
“…The amber stop codon was placed at site K529 of fLuc (fLuc529TAG-rLuc) where a critical lysine residue orients the substrate and stabilizes the adenylated substrate during catalysis through a hydrogen bonding interaction with the phosphate oxygen. 29 Caging this lysine blocks enzymatic activity and small molecule-induced decaging results in full activation of fLuc through formation of the wild-type active site (Figure 2B). 30 Previous studies of decaging PABK with a panel of phosphines in mammalian cells found that 2-(diphenylphosphinyl)benzamide (2DPBM) showed the fastest reaction rate and no toxicity.…”
Section: Tcokmentioning
confidence: 99%